Reproduction of the Golden Apple Snail (Ampullaridae) Egg Mass, Hatching and Incubation - Lacanilao, Flor (1990)
Reproduction in the golden apple snail(Apullarius sp.) was studied to provide breeding information for laboratory and field culture. The influence of food quality and some environmental conditions in egg properties were studied in the laboratory at normal temperatures. Wandering jew produced the most numerous egg masses ; combination of wandering jew and kangkong, the shortest incubation period; and duckweed, the highest hatching rate and the best overall effects on these egg properties. Water changed affected number of egg masses at higher stocking density, but affected egg mass size at all stocking densities and sex ratios, seasonal or natural temperature affects were only seen on incubation period- shortest in the warm months of April and May but longest in the cool months of December-February. Increasing age decreased the number and size of egg masses and hatching rate, but did not affect the incubation period. The results of the study can guide snail culturists, and may contribute to solution of snail pest problems now facing rice farmers.